Software piracy - Sigler, David (UKM, Bangi : Perpustakaan Tun Seri Lanang, 1996)
The video talks on software piracy.
The talk was held in conjuction with'Minggu Perpustakaan UKM', 9-13 Jan., 1996, Bangi.
Copy available in DVD format.
Keywords: Software protection; Computer crimes